Building words and phrases in the left temporal lobe. (September 2018) - Flick, Graham; Oseki, Yohei; Kaczmarek, Amanda R.; Al Kaabi, Meera; Marantz, Alec; Pylkkänen, Liina
Abstract: A central part of knowing a language is the ability to combine basic linguistic units to form complex representations. While our neurobiological understanding of how words combine into larger structures has significantly advanced in recent years, the combinatory operations that build words themselves remain unknown. Are complex words such as tombstone and starlet built with the same mechanisms that construct phrases from words, such as grey stone or bright star ? Here we addressed this with two magnetoencephalography (MEG) experiments, which simultaneously varied demands associated with phrasal composition, and the processing of morphological complexity in compound and suffixed nouns. Replicating previous findings, we show that portions of the left anterior temporal lobe (LATL) are engaged in the combination of modifiers and monomorphemic nouns in phrases (e.g., brown rabbit ). As regards compounding, we show that semantically transparent compounds (e.g., tombstone ) also engage left anterior temporal cortex, though the spatiotemporal details of this effect differed from phrasal composition. Further, when a phrase was constructed from a modifier and a transparent compound (e.g., granite tombstone ), the typical LATL phrasal composition response appeared at a delayed latency, which follows if an initial within-word operation ( tomb + stone ) must take place before the combination of the compound with the preceding modifier ( granite  +  tombstone ). In contrast to compounding, suffixation (i.e., star  +  let ) did not engage the LATL in any consistent way, suggesting a distinct processing route. Finally, our results suggest an intriguing generalization that morpho-orthographic complexity that does not recruit the LATL may block the engagement of the LATL in subsequent phrase building. In sum, our findings offer a detailed spatiotemporal characterization of the lowest level combinatory operations that ultimately feed the composition of full sentences.